The Role of Motivation on Performance with Job Satisfaction as a Mediation Variable - Suwandana, I Made Adi; Perdanawati, Luh Putu Virra Indah (International Journal of Social Science and Business, 2020)
This study aimed to analyze intrinsic motivation and extrinsic motivation on employee job satisfaction and employee performance, the effect of employee job satisfaction on employee performance, the effect of intrinsic motivation and extrinsic motivation on employee performance with employee job satisfaction as a mediating variable at the People's Credit Bank. The population in this study was 687 employees at 13 BPRs. The number of research samples using proportional stratified random sampling method is 175 employees. Hypothesis testing in this study used path analysis. The results of the analysis showed that the influence of intrinsic motivation on employee performance with employee job satisfaction as a mediating variable obtained z count of 3,335 and the influence of extrinsic motivation on employee performance with employee job satisfaction as a mediating variable obtained z count of 3,378. Based on these findings, it can be concluded that there is a positive influence of intrinsic and extrinsic motivation on employee performance with job satisfaction as a mediating variable.